Effect of Liquidity, Profitability, Firm Size on Firm Value with Capital Structure as Intervening Variable - Andini Nurwulandari (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
The purpose of this study is to analyze and obtain empirical evidence of the effect of liquidity, profitability, firm size on firm value with capital structure as an intervening variable. The population in this study were manufacturing companies in the primary industry and chemical subsectors listed on the Indonesia Stock Exchange for 2014-2019, with a sample size of 19 companies and using the purposive sampling method. Furthermore, the data were collected quantitatively using multiple regression using the SmartPLS v.3.2.8. This study indicates that liquidity, profitability, and firm size directly have a negative and significant effect on capital structure; liquidity directly has a negative and insignificant influence on firm value. Profitability and firm size directly have a positive and not significant impact on firm value. Capital structure has a negative and significant effect directly. And then, the capital structure can mediate the effect of liquidity, profitability, company size on company value.